Corticosteroid Weaning in Stable Heart Transplant Patients: Guidance by Serum Cortisol Level - David A. Baran; Cheryl Rosenfeld; Mark J. Zucker (Journal of Transplantation)
Background. Despite earlier studies describing the feasibility of steroid weaning in heart transplant patients, the majority of patients are maintained on steroid therapy for life. We examined a strategy based on a single morning serum cortisol measurement. Methods. We assigned stable posttransplant patients, who were maintained on tacrolimus, mycophenolate mofetil, and corticosteroids, into one of two groups based on a screening morning cortisol level. Patients with a cortisol < 8 micrograms/deciliter were assigned to a “maintenance” group and the others were assigned to the weaning group and steroids were tapered off over 4–6 weeks. Patients were monitored on subsequent office visits for adrenal insufficiency and allograft rejection. Results. Thirty-one patients were enrolled (6 patients in the maintenance group and 25 in the steroid-weaning group). Mean follow-up was 10.2±4 years for the weaning group and 9.0±4.9 years in the maintenance group (p=0.6). No cases of rejection were noted, nor did any patient resume steroid treatment following discontinuation. Conclusion. Steroids can be safely discontinued in stable heart transplant patients with an AM serum cortisol ≥ 8 micrograms/deciliter with appropriate outpatient follow-up. In this study, no patient suffered late rejection or clinically noted adrenal insufficiency.